Esophagogastroduodenoscopy findings in patients on the waiting list for bariatric surgery - Arieira, Cátia (2019)
Background: Bariatric surgery (BS) is one of the most effective approaches to weight loss. Performing esophagogastroduodenoscopy (EGD) prior to BS is controversial but allows the detection and treatment of mucosal lesions that may affect surgical decision and type of surgery. Aim: The aim of this study was to identify the frequency of gastric lesions and Helicobacter pylori (Hp) infection in a group of asymptomatic patients on the waiting list for BS. Methods: This is a retrospective descriptive study including patients undergoing EGD before BS. Results: A total of 360 patients were included with a mean age of 42.1 ± 10.8 years, 319 (88.6%) were females, with a mean body mass index of 42.8 ± 5.44 kg/m2. Regarding endoscopic findings, 25.6% presented no endoscopic lesions, 61.6% presented hyperemic gastropathy, 11.4% erosive gastropathy, 1.1% gastric polyp, and 0.3% gastric ulcer. Histologically, no changes were observed in 20.8% of the patients, 239 (66.4%) presented with superficial gastritis, 11.7% (n = 42) had chronic atrophic gastritis and intestinal metaplasia (n = 34 in the antrum, n = 1 in the body, and n = 7 in both the antrum and the body), and 1.7% (n = 6) had low-grade dysplasia. Hp was positive in 251 (69.7%) patients. We found that patients with metaplasia or dysplasia were more frequently submitted to surgical techniques that did not exclude the stomach (55.8 vs. 16.4%, p < 0.001). Conclusion: EGD with histological analysis plays an important role in the pre-surgical evaluation in BS, with a high rate of pathological findings in asymptomatic patients. These findings may have an impact on the long-term management and outcomes of these patients.